Comparison of Enzyme Immunoassay and Latex Agglutination Methods for Detection of Cryptococcus neoformans Antigen - Scott, E. Nan; Muchmore, Harold G.; Felton, Frances G. (American journal of clinical pathology, 1980)
An enzyme immunoassay for the measurement of cryptococcal capsular polysaccharide in human body fluids is described. The enzyme immunoassay detects cryptococcal capsular polysaccharide at a concentration of 6 ng/ml, compared with 35 ng/ml detectable by the latex agglutination test. The enzyme immunoassay detects cryptococcal capsular polysaccharide in body-fluid specimens that are negative by the latex agglutination test. Titers by enzyme immunoassay are generally higher and persist longer into the treatment period than those determined by latex agglutination. No cryptococcal capsular polysaccharide is detected by the enzyme immunoassay procedure in fluids from subjects not known to have cryptococcosis. The enzyme immunoassay procedure presented here provides earlier detection of cryptococcal material in body fluids, and thereby diagnosis and treatment of cryptococcosis can be made earlier in the course of disease.